A mass-tagged MOF nanoprobe approach for ultra-sensitive protein quantification in tumor-educated platelets. Issue 51 (7th June 2022) - Chen, Xiuyu; Zhu, Jianhua; Sun, Bo; Zhang, Xian; Hu, Yechen; Chen, Yun
Abstract : A mass-tagged metal–organic framework (MOF) nanoprobe approach was developed for ultra-sensitive quantification of the target protein in blood platelets. Abstract : A mass-tagged metal–organic framework (MOF) nanoprobe approach was developed for ultra-sensitive quantification of platelet protein CD44 by integrating activable aptamer recognition and MOF nanoprobe signal amplification with mass spectrometric detection. This approach offered high sensitivity and quantitative capability for low abundant protein analysis in tumor-educated platelets (TEPs), exhibiting great potential in cancer diagnosis and management.